2001
DOI: 10.1046/j.1365-2273.2001.00513.x
|View full text |Cite
|
Sign up to set email alerts
|

Helicobacter pylori and tonsillectomy

Abstract: Tonsillar tissue is a component of mucosa-associated lymphoid tissue (MALT), which has evolved to protect vulnerable mucosal surfaces. Helicobacter pylori, implicated as an aetiological factor in duodenal ulcers and gastritis, induces the appearance of lymphoid aggregates (MALT) in the stomach. This organism is cytotoxic via a nitric oxide synthase cascade. The possibility that tonsillar tissue processes Helicobacter pylori or that Helicobacter pylori can colonize the palatine tonsils is explored. The study de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
33
1

Year Published

2003
2003
2018
2018

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 47 publications
(36 citation statements)
references
References 28 publications
2
33
1
Order By: Relevance
“…Detection of H. pylori from tonsil or adenoid tissues has been studied by a number of other investigators using CLO or PCR. Some researchers did not detect any H. pylori (di Bonaventura et al 2001;Skinner et al 2001;Yilmaz 2004), whereas the other reported various percentages for the presence of the pathogen, even higher than reported in the present study (Unver et al 2001;Cirak et al 2003). The difference observed between those studies may be due to particular characteristics of population or diversity of the methods used.…”
Section: Discussioncontrasting
confidence: 84%
“…Detection of H. pylori from tonsil or adenoid tissues has been studied by a number of other investigators using CLO or PCR. Some researchers did not detect any H. pylori (di Bonaventura et al 2001;Skinner et al 2001;Yilmaz 2004), whereas the other reported various percentages for the presence of the pathogen, even higher than reported in the present study (Unver et al 2001;Cirak et al 2003). The difference observed between those studies may be due to particular characteristics of population or diversity of the methods used.…”
Section: Discussioncontrasting
confidence: 84%
“…pylori is known to be involved in the pathogenesis of various disease conditions, including duodenal ulcers, gastric conditions, IgA nephropathy and gastric adenomas with various host reservoirs acting as a nidus for continued persistence of the organism [3]. The human palatine tonsil has been proposed as one of the extra gastric reservoirs of H. pylori and various studies have been undertaken to study its role [7][8][9][10][11]. Other studies dispute the fact that the human palatine tonsil may be an extragastric reservoir of H. pylori [12,13].…”
Section: Introductionmentioning
confidence: 99%
“…Some researchers stated that H. pylori plays a role in the pathogenesis of chronic adenotonsillitis. 3,13 But others demonstrated that there are no such association. Hence this study was aimed to find out the prevalence of H. pylori in tonsillar tissue of patients with chronic tonsillitis by rapid urease test in a tertiary hospital in Kerala.…”
Section: Introductionmentioning
confidence: 99%